EFFECT OF HONEY SUPPLEMENTATION ON BREAST MILK PRODUCTION AMONG POSTPARTUM MOTHERS: A QUASI-EXPERIMENTAL STUDY - nining istighosah (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
Background: Insufficient breast milk production remains one of the most common challenges encountered by postpartum mothers and contributes to the suboptimal achievement of exclusive breastfeeding. Adequate maternal nutrition is essential for supporting lactation, and honey has attracted increasing attention as a natural complementary nutritional supplement because it contains carbohydrates, amino acids, vitamins, minerals, antioxidants, and bioactive compounds that may improve maternal metabolism and stimulate breast milk production.Objective: This study aimed to determine the effect of honey supplementation on breast milk production among postpartum mothers.Methods: A quasi-experimental study employing a one-group pretest–posttest design was conducted at the Independent Midwifery Practice (TPMB) of Ida Siswi Astuty, West Kotawaringin Regency, Central Kalimantan, Indonesia, from November to December 2024. Thirty postpartum mothers were recruited using accidental sampling. Honey supplementation was administered for nine consecutive days. Breast milk production was measured before and after the intervention using breast milk pumping measurements and structured observation sheets. Data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test because the data were not normally distributed.Results: The mean breast milk production increased from 49.17 ± 18.62 mL before the intervention to 136.83 ± 31.66 mL after honey supplementation, representing an average increase of 87.66 mL. Statistical analysis revealed a significant difference between pre- and post-intervention measurements (Z = −4.792; p < 0.001), indicating that honey supplementation significantly improved breast milk production among postpartum mothers.Conclusion: Honey supplementation significantly increased breast milk production in postpartum mothers. As a natural, affordable, and culturally acceptable nutritional intervention, honey may be incorporated into postpartum care to support successful breastfeeding and exclusive breastfeeding programs. Further randomized controlled studies with larger sample sizes are recommended to strengthen the current evidence.